Suspected Primary Spontaneous Asymptomatic Pneumothorax in a Cat - Michael Sliman; Adam J. Rudinsky; Sarah Lumbrezer; Jenessa A. Winston; Valerie J. Parker; Sarah Lorbach; James Howard (Case Reports in Veterinary Medicine)
Spontaneous pneumothorax (SPT) is a documented emergency of the respiratory tract condition classified as either primary or secondary based on the presence of underlying pulmonary conditions. All reported SPT in the feline literature are evaluated for respiratory clinical signs. Primary SPT without underlying pathology or without clinical signs is not reported in cats. This case report describes a 10-year-old domestic longhair cat that was referred for evaluation of chronic lethargy with severe azotemia and placement of a subcutaneous ureteral bypass (SUB) system. Prior to presentation, the cat was diagnosed with renal insufficiency and treated medically with no resolution. Clinical examination under sedation revealed right-sided renomegaly. Thoracic radiographs revealed gas in the caudodorsal pleural space and concurrent pulmonary atelectasis. No respiratory clinical signs were present. Thoracic CT showed two pulmonary bullae, one located in the right caudal lung lobe and one in the cranial segment of the left cranial lung lobe. Abdominal ultrasound showed a right-sided ureteral obstruction. Medical management was elected for the spontaneous pneumothorax. A SUB was placed to address the ureteral obstruction; no complications were noted during recovery. The cat was free of clinical signs of respiratory disease after a follow-up time of nine months. This is the first reported case of a cat diagnosed with a nonclinical suspected primary spontaneous pneumothorax with no concurrent predisposing pulmonary pathology.